A Model for the Flow of Blood in Capillaries - Choksi, Armeane (My University, 1969)
A new constitutive equation has been developed for the flow of blood through capillaries. Pressure drop and volume flow data of Haynes and Burton and Merrill et al. have beer utilized in this development for a range of radii from 57.04 micra to 747.4 micra and a hematocrit range of 8.8% to 82.5%. A comparison has been made with the Casson equation used by Merrill and Pelletier and the advantage of this new equation over the Casson equation has been verified. The usual assumption of no-slip-at-the-wall has been verified to be valid, up to a hematocrit level of 39.3%.
Keywords: model; blood flow; capillaries